Clinical and epidemiological profile of congenital syphilis at a neonatal reference center in the state of Pará-Brazil: An analysis from 2019 to 2024 (Research, Society and Development, 2026)
Objective: To analyze the clinical and epidemiological profile of newborns diagnosed with congenital syphilis at a reference neonatal center in the state of Pará, Brazil, from 2019 to 2024. Methods: A retrospective, descriptive, single-center cohort study based on the analysis of medical records and Live Birth Certificates of neonates diagnosed with congenital syphilis (ICD A50), born at the Fundação Santa Casa de Misericórdia do Pará (FSCMPA). The variables analyzed included neonatal characteristics (sex, race, birth anthropometry, Apgar score from the 1st to the 5th minute, and presence of congenital anomalies) and maternal characteristics (age group, educational level, obstetric history and current pregnancy). Results: A total of 309 eligible medical records were analyzed, showing annual variation in case numbers over the study period and a marked increase in notifications in 2023, which accounted for 141 cases (45.6%). Most newborns presented adequate anthropometric measurements at birth; however, 42.7% showed values below normal ranges. Apgar scores from the 1st to the 5th minute were satisfactory, and congenital anomalies were infrequent but clinically relevant. The maternal profile was predominantly characterized by young women with low educational attainment and an insufficient number of prenatal visits. Conclusion: Congenital syphilis remains an important public health concern in the Amazon region, reflecting persistent gaps in prenatal care and social inequalities. These findings reinforce the need to strengthen screening policies, timely treatment, and epidemiological surveillance to reduce vertical transmission and its neonatal impacts.